A LITERATURE REVIEW OF TELEMEDICINE IN INDONESIA: PAST, PRESENT, AND FUTURE PROSPECTIVE - Jeremiah Hilkiah Wijaya; Gilbert Sterling Octavius; Lie Rebecca Yen Hwei (Universitas Airlangga, 2022)
Background: Indonesia has a great potential in the development of digital health technologies. However, several challenges might also arise in hand with the development of telemedicine. Aims: We aimed to conduct a literature review of the use of telemedicine in Indonesia in order to know how the start is, the development, and future considerations of its usage. Methods: From the digital databases of PubMed, Google Scholar, and Neliti (Indonesia's Research Repository), each author completed literature searches of telemedicine in Indonesia from 1985 to 2021. Results: A total of 8 studies were included in current literature review. In 1985-1987, Indonesia undertook the first satellite-based telemedicine. During the early twenty-first century, rapid improvements in information technology have expanded to other industries, including health care through telemedicine. Covid-19 dilemma compels physicians to adopt. Through telemedicine, many is experienced the benefit during the pandemic. However, in developing telemedicine system for the future, the use of telemedicine has several challenges, namely related to human resources, infrastructure and ethical regulations. Conclusion: When telehealth is successfully implemented in Indonesia, it will benefit both the developer and the consumer. Despite the benefits, the challenge of implementing and developing a comprehensive eHealth environment in Indonesia might be seen as tremendous, given that the country is currently developing its infrastructure.